2020
DOI: 10.1177/2042753020926948
|View full text |Cite
|
Sign up to set email alerts
|

A practitioner framework for blended learning classroom inquiry-based virtual reality lessons

Abstract: This article presents the Blended Learning Virtual Reality Inquiry Framework, an original framework for creating virtual reality inquiry-based lessons for the modern technology-driven classroom. The framework shared in this article invokes research on blended learning , experiential learning, and inquiry-based learning to structure a virtual reality-specific lesson model. The authors present the theory and research behind each aspect of the framework before explaining how the framework is used. The article con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…However, while an increasing corpus of studies has reported on the use of VR simulations in order to engage students with inquiry-based learning (Barab et al, 2000;Hansen et al, 2004;Kim, 2006;Shin, 2002;Wu et al, 2019), what still remains unclear is 'how' VR simulations, and especially immersive VR simulations, should be integrated in the inquiry-based learning process and what are the effects of students' learning experiences-encompassing immersive VR simulations-on their understanding of physical phenomena and concepts. This can be attributed to the fact that immersive VR is a new technology to the classroom and thus, in inquiry-based learning as well (Fegely et al, 2020).…”
Section: Technology-enhanced Inquiry-based Learningmentioning
confidence: 99%
“…However, while an increasing corpus of studies has reported on the use of VR simulations in order to engage students with inquiry-based learning (Barab et al, 2000;Hansen et al, 2004;Kim, 2006;Shin, 2002;Wu et al, 2019), what still remains unclear is 'how' VR simulations, and especially immersive VR simulations, should be integrated in the inquiry-based learning process and what are the effects of students' learning experiences-encompassing immersive VR simulations-on their understanding of physical phenomena and concepts. This can be attributed to the fact that immersive VR is a new technology to the classroom and thus, in inquiry-based learning as well (Fegely et al, 2020).…”
Section: Technology-enhanced Inquiry-based Learningmentioning
confidence: 99%
“…Kashefi et al (2012) also emphasized that blended learning contributes to students' communication and teamwork skills. As technology advances, classroom and classroom management approaches change, leading to a shift in the role of teachers (Fegely et al, 2020). Teachers are moving away from being mere intermediaries between knowledge and students.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Siendo significativo que la investigación sobre el aprendizaje combinado, el aprendizaje experiencial y el aprendizaje basado en la investigación, son pertinentes para estructurar un modelo de lección específico de realidad virtual (Fegely et al 2020).…”
Section: Discussionunclassified